Criminal Regulations Related to Illegal Migration Once and Now - Gal, Istvan Laszlo; Nagy, Melania (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
In 2015, Europe had to face a huge societal crisis. Numerous people left behind their homeland for safer living conditions. The problem started right here, foreign people arrived without legal documents, their identification was unimaginable. Immigrants have brought together all the social, economic, and health problems as well. This situation creates uncertainty in the host countries. Hungarian legislators had to create new regulations which can protect our borders. In this context, new criminal offenses have been introduced such as blocking the border lock (Btk.352./A), damaging a deadline (Btk. 352./B) and obstructing the construction work on the border guard (Btk.352/C). Actually, is that sections are recent in C of 2012 Act, or just revivification of some acient law from the past?